2012
DOI: 10.4000/discours.8673
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Pattern Language Approach to Document Description

Abstract: Pattern libraries, originating in architecture, are a common way to share design solutions in interaction design and software engineering. Our aim in this paper is to consider patterns as a way of describing commonly-occurring document design solutions to particular problems, from two points of view. First, we are interested in their use as exemplars for designers to follow, and second, we suggest them as a means of understanding linguistic and graphical data for their organization into corpora that will facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The notion of pattern language, coined by the architect Christopher Alexander, advocates the search for functional, pattern-based solutions to specific design problems. Examining the relation between design patterns and genres, Waller et al (2012) note that similar patterns may be found in different genres, which implies the kind of flexibility of movement across the genre space theorised within the GeM framework.…”
Section: Extensions and Inspirationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of pattern language, coined by the architect Christopher Alexander, advocates the search for functional, pattern-based solutions to specific design problems. Examining the relation between design patterns and genres, Waller et al (2012) note that similar patterns may be found in different genres, which implies the kind of flexibility of movement across the genre space theorised within the GeM framework.…”
Section: Extensions and Inspirationsmentioning
confidence: 99%
“…Extensions of the GeM framework have not been limited to media, but also include theoretical and methodological openings as well. To exemplify, Waller et al (2012) build on the GeM framework and the previous work in Waller (1987) to explore the notion of 'pattern language' in information design. The notion of pattern language, coined by the architect Christopher Alexander, advocates the search for functional, pattern-based solutions to specific design problems.…”
Section: Extensions and Inspirationsmentioning
confidence: 99%
“…Inspired by Alexander's initial work, pattern libraries have become a way to share solutions, not only for architects, but also for interaction designers, software engineers, and information designers (e.g., Pan & Stolterman, 2013;Tidwell, 2014;Waller & Delin, 2011). Borrowing tools from these professions seems a natural continuation of the metaphor of contracts as interfaces.…”
Section: A Design Patterns Approach For Contractsmentioning
confidence: 99%
“…Originating in architecture (Alexander et al, 1977), design patterns have become widely used in software engineering and interface design (Tidwell, 1999), and in more recent times, among some information designers (Farkas et al, 2011; Waller et al, 2012). Gerding (2013) proposed a design pattern approach to contract content, and Haapio and Hagan (2016) have proposed a pattern library for contract design.…”
Section: Communicating What We Did: Design Patterns For Clearer Contrmentioning
confidence: 99%